Social Capital Dimensions and Civil Society: Inclusive vs. Exclusionary Social Capital in Sport Governance - Patsantaras, Nikolaos; Irene Kamberidou (Presentation at the international conference “Social Capital and Sport Governance in Europe: Trust and the Use of Social Ties”,4-5/12/2006, organized by the Universitat Commerciale Luigi Bocconi and IPAS-Institute of Public Administration and Health, 2006)
Presented by Irene Kamberidou  5/12/2006: Patsantaras, N., & Kamberidou, I. (2006). "Social Capital Dimensions and Civil Society: Inclusive vs. Exclusionary Social Capital in Sport Governance". Presentation at the international conference “Social Capital and Sport Governance in Europe: Trust and the Use of Social Ties”,4-5/12/2006, organized by the Universitat Commerciale Luigi Bocconi and IPAS-Institute of Public Administration and Health. Universitat Commerciale Luigi Bocconi and IPAS-Institute of Public Administration and Health Care Management ‘Carlo Masini’ in collaboration with the European Commission, Milano Italy.  DOI: 10.13140/RG.2.1.2700.4644 [ K.5 in Apella  and  K.5.1 in Apella ]